Towards Blockchain-based Learning Management System for Adaptive Self-regulation Development in ELT - Saadati, Zohreh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The study of online higher education learning and academic achievement has increasingly emphasized self-regulated learning (SRL). Few studies so far have investigated the blockchain-based learning management system (LMS) and adaptive SRL intervention in English Language Teaching (ELT) online higher education. This study aimed to develop a blockchain-enabled LMS as a metacognitive tool in ELT online higher education with SRL adaptive intervention to improve planning, monitoring, reflection, collaboration, zone of proximal development (ZPD), and scaffolding towards self-regulation development and learning achievement. To do that, based on the benchmark data of 33 ELT Master of Art (MA) students, the blockchainbased LMS is developed that provided three phases of planning, action, and reflection SRL adaptive intervention throughout the ELT MA online program. Data were collected quantitatively by utilizing SRL pre- and post-test questionnaire which were analyzed along the t-test and qualitatively by adopting reflective essays and semistructured interview which were analyzed through the content analysis method. The findings and the development of the blockchain-based LMS with adaptive SRL intervention contributed to the development of ELT MA students’ SRL skills in realistic goal setting, self-monitoring, self-reflection, and self-awareness through SRL adaptive intervention in planning, monitoring, reflection, ZPD, and collaboration. Also, ELT MA instructors tracked students’ activities and in case of failure to comply with SRL adaptive interventions, they could provide feedback to the students. In addition, this study showed that the integration of blockchain technology in ELT online higher education with adaptive SRL appears to be a promising trend in the development of SRL.

ÖZ: Çevrimiçi yükseköğretim öğrenme ve akademik başarı çalışması, öz-düzenlemeli öğrenmeyi giderek daha fazla vurgulamaktadır. Şimdiye kadar çok az çalışma blok zinciri tabanlı öğrenme-yönetim sistemini (LMS) ve İngiliz Dili Öğretimi (ELT) çevrimiçi yükseköğretiminde öz-düzenlemeli öğrenmeyi uyumlaştıracak müdahale programlarını araştırmıştır. Bu çalışma, öz-düzenlemeli öğrenmeyi uyumlaştıracak müdahale programları ile çevrimiçi ELT yüksek lisans öğretiminde üst bilişsel bir araç olarak blok zinciri etkin bir öğretim ve yönetim sistemini geliştirmeyi hedeflemiştir. Bu müdahale programı özellikle planlamayı, izlemeyi, yansıtmayı, işbirliğini, yakınsal gelişim bölgesini ve yakınsal gelişim bölgesi içerisindeki destekleyici araçları (scaffolding) öz-düzenlemeyi ve öğrenmeyi geliştirecek şekilde etkinleştirmeyi amaçlamaktadır. Bunu yapmak için, 33 ELT yüksek lisans öğrencisinin karşılaştırma verilerine dayanarak, ELT MA çevrimiçi programında öz-düzenlemeli öğrenmeyi uyumlaştıracak müdahale programının üç aşaması olan planlama, eylem ve yansıtmayı sağlayan blok zincir tabanlı bir öğrenme yönetim sistemi geliştirilmiştir. Nicel veriler, t-testi ile analiz edilen öz-düzenlemeli ön ve son-test anketi kullanılarak, nitel veriler ise içerik analizi yöntemi kullanılarak analiz edilen katılımcıların yazdığı yansıtıcı kompozisyonlar ile elde edilmiştir. Öz-düzenlemeli öğrenmeyi uyumlaştıracak müdahale programı ile blok zinciri tabanlı öğretim yönetim sisteminin geliştirilmesi, ELT MA öğrencilerinin gerçekçi hedef belirleme, kendi kendini izleme, yansıtma ve öz farkındalık konularında öz-düzenlemeyi uyumlaştıracak program müdahalesinin planlama, izleme, yansıtma, yakınsal gelişim bölgesi ve iş birliği ile öz-düzenlemeli öğrenme becerilerinin gelişimine katkıda bulunmaktadır. Ayrıca, ELT MA öğretim elemanları öğrencilerin etkinliklerini takip edebilecek ve öz-düzenlemeli öğrenmeyi uyumlaştıracak programların müdahalelerine uyulmaması durumunda öğretmenler öğrencilere geri bildirim sağlayabilecektir. Ek olarak, bu çalışma, blok zinciri teknolojisinin ELT çevrimiçi yüksek öğrenimine uyarlanabilir öz-düzenlemeli öğrenme ile entegrasyonunun, öz-düzenlemeyi uyumlaştıracak bir müdahale programı geliştirilmesinde umut verici bir yenilik olduğunu göstermiştir.
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2021. Supervisor: Assoc. Prof. Dr. Canan Zeki.
Keywords: Thesis Tez; English Language Teaching (ELT) Department; Foreign Language Education; English Language Teaching; Adaptive learning; blockchain technology; collaborative learning; learning management system; metacognitive tools